مسؤولية القائم بالإتصال من منظور الإعلام الإسلامي - دراسة تأصيلية - بن سديرة, فاطمة (University of Eloued جامعة الوادي, 2017)
تمحورت إشكالية الدراسة حول مسؤولية القائم بالاتصال من منظور الإعلام الإسلامي، وتطرقت في ذلك إلى دراسة القائم بالاتصال كإعلامي من خلال الشروط الواجب توفرها فيه، وتناولت أهم العوامل المؤثرة فيه، وذكرت أبرز الضوابط في ممارسته الإعلامية، ودراسة البعض من مسؤولياته كالمسؤولية الأخلاقية والدينية والاجتماعية، وذكرت محددات كل مسؤولية على حدى، بالإضافة إلى دراسته كداعية إسلامي من حيث الصفات ومقوماته الأخلاقية والاستدلال لها بآيات قرآنية وبأحاديث نبوية، ومعرفة مختلف ثقافاته كالثقافة الإسلامية والأدبية اللغوية، والثقافة التاريخية والواقعية. والتطرق كذلك إلى معرفة الدور الدعوي للداعية المسلم ووسائل تبليغ رسالته والعوامل المؤثرة في تنمية شخصيته، معتمدة في ذلك على المنهج الاستقرائي حيث قمت باستقراء بعض العناوين من خلال الاستدلال لها ببعض الآيات القرآنية والأحاديث النبوية بهدف توضيح المعنى والمفهوم. للوصول إلى النتائج المرجوة ولعل أبرزها ما يلي: على القائم بالاتصال معرفة الشروط الواجب توفرها فيه من مهارات الاتصال وإدراك اتجاهاته وطبيعة أدواره التي يؤديها ومعرفة ضوابط رسالته الإعلامية وإدراكها. إن القائم بالاتصال يستمد مقوماته ومسؤولياته المختلفة من مصادر شريعته الإسلامية وفق منهج إسلامي صحيح. The present study is centered on the communicator from the perspective of Islamic Media. It discussed the conditions that the communicators as media experts should qualified with and the most important factors that might influence them as well as the rules that govern this profession. Our study tackles also some of their tasks as the moral, religious and social ones. It highlights every and each feature of the latter tasks. The present study examines the communicators as preachers: it talks about their role and requirements and proves that with some verses from the Quran and some other sayings from the prophetic Hadeeths. We seek also to identify to what extent are they versed in Islamic culture, in Arabic language, in History and in particular in their societies very facts. Besides, it tackles the role performed by those preachers and the various factors influencing their very personalities. We rely upon the descriptive method as it is aiming at identifying the above-mentioned aims that may lead us to the following findings: The communicators should be both aware of the conditions required, the communication skills, and be also skillful in doing the tasks they are required to. The communicator as a Muslim preacher inspires all his/her tasks and perspectives from the Islamic sharia according to the true rules of Islam
مذكرة ماستر تخصص دعوة واعلام
Keywords: المسؤولية – القائم بالاتصال – الإعلام الإسلامي – البعد الأخلاقي; Responsibility - Communicator - Islamic Media - Ethical Dimension